2021
DOI: 10.1140/epjc/s10052-020-08802-1
|View full text |Cite
|
Sign up to set email alerts
|

Stability of charged thin-shell gravastars with quintessence

Abstract: This paper develops a new solution of gravitational vacuum star in the background of charged Kiselev black holes as an exterior manifold. We explore physical features and stability of thin-shell gravastars with radial perturbation. The matter thin layer located at thin-shell greatly affects stable configuration of the developed structure. We assume three different choices of matter distribution such as barotropic, generalized Chaplygin gas and generalized phantomlike equation of state. The last two models depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…There are many researchers that extended the range of B0(D)$B_0(D)$ to discuss the stability of developed structure. [ 104, 105, 106 ]…”
Section: Thin‐shell Formalism Around a Traversable Wormholementioning
confidence: 99%
See 3 more Smart Citations
“…There are many researchers that extended the range of B0(D)$B_0(D)$ to discuss the stability of developed structure. [ 104, 105, 106 ]…”
Section: Thin‐shell Formalism Around a Traversable Wormholementioning
confidence: 99%
“…The proper length can be evaluated as [105, 106] lbadbreak=DD+εdD2n2(Da0a1a2)+(lnfalse(Dfalse)lnfalse(r0false))(a0lnfalse(Dfalse)+2nfalse(a0+a1false)+a0lnfalse(r0false))2Dn2.\begin{equation} l=\int _{D}^{D+\epsilon } \frac{dD}{\sqrt {\frac{2 n^2 (D-a_0-a_1-a_2)+(\ln (D)-\ln (r_0)) (-a_0 \ln (D)+2 n (a_0+a_1)+a_0 \ln (r_0))}{2 D n^2}}}. \end{equation}where ε represents the thickness of the shell and ε1$\epsilon \ll 1$.…”
Section: Thin‐shell Formalism Around a Traversable Wormholementioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the developed structure shows stable behavior near the formation of the event horizon for suitable values of the physical parameters. Recently, we have constructed thin-shell gravastar from exterior regular as well as charged Kiselve BHs and explored the stability of the developed geometry through radial perturbation by considering variable EoS [18].…”
Section: Introductionmentioning
confidence: 99%